Legislative Approaches of Protection of Foreign Investment in Nepal and Ways of Minimizing the Ambit of Challenges - Ghimire, Saroj K (KDCBAR Law Journal, 2025)
Nepal witnessed multiple political transition and constitutional development over seven decades. Nepal retains one of the youngest constitutions in the world with most federal and democratic nature being oriented to socialism economy. Despite various political transitions and stability from last decade after the promulgation of the Constitution of Nepal, 2015, the county could not ensure the expected level of economic progress regardless of understanding that foreign investment is one of the pillars of economic progress. The Constitution of Nepal, 2015 and the new Foreign Investment and Technology Transfer Act, 2019 recognized the importance of foreign investment for overall economic development. Likewise, the largest foreign investment retaining countries like China and India have made a liberal, stable, fair, transparent and accountable regime to promote and protect foreign investment. However, in Nepalese context, despite having friendly environment commitments, there is no remarkable step taken to manage challenges that have surfaced at all levels regardless of having ample of areas wherein foreigner can make investment as FITTA has opened and various protection mechanism are tendered. This article analyzes foreign investment scenario of Nepal by evaluating the modes, protection mechanism and challenges and extends the possible means of reforms.